2004
DOI: 10.1111/j.0022-2445.2004.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Have No Time: Daily Rhythms and the Organization of Time for Low‐Income Families*

Abstract: Using ethnographic data from Welfare, Children, and Families: A Three-City Study, we examined time obligations and resource coordination of low-income mothers. Longitudinal data from 75 African American, Hispanic, and non-Hispanic White families residing in Chicago, including information on daily routines, perceptions of time, and access to resources, were gathered via participant observation and intensive semistructured interviews over 4 years. Results indicated that families constantly improvised daily rhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 20 publications
2
120
0
Order By: Relevance
“…As Table 1 shows, households in the bottom income quintile have a higher combined housing and transportation expenditure burden than the average for all households. Many individuals in households without automobiles make some of their trips by automobile (Pucher & Renne, 2001), and a subset even pay for these auto trips in the form of taxi fares or compensation to friends and family for rides (Giuliano & Moore, 1999;Lovejoy & Handy, 2011;Rogalsky, 2010;Roy, Tubbs, & Burton, 2004). Nonetheless, their more infrequent use of automobiles helps to explain why low-income families spend less on travel than higher income households.…”
Section: The Transportation Expenditure Burdenmentioning
confidence: 99%
“…As Table 1 shows, households in the bottom income quintile have a higher combined housing and transportation expenditure burden than the average for all households. Many individuals in households without automobiles make some of their trips by automobile (Pucher & Renne, 2001), and a subset even pay for these auto trips in the form of taxi fares or compensation to friends and family for rides (Giuliano & Moore, 1999;Lovejoy & Handy, 2011;Rogalsky, 2010;Roy, Tubbs, & Burton, 2004). Nonetheless, their more infrequent use of automobiles helps to explain why low-income families spend less on travel than higher income households.…”
Section: The Transportation Expenditure Burdenmentioning
confidence: 99%
“…While similar patterns relating indices of chaos to child development outcomes have been shown in both highincome western and low-income non-western cultures (Wachs & Corapci, 2003) and the CHAOS scale has been used successfully in Pakistan (Tus-Sabah et al, 2011) as well as with low income Latino families in the United States (Haack et al, 2011), culturally driven parental norms, preferences and belief systems can influence the degree to which parents perceive their environment as chaotic or not (Wachs & Corapci, 2003;Weisner, 2010). Given that the concept of a chaotic environment can be seen across multiple cultures (Weisner, 2010) cultural or demographic differences may be may be more qualitative than quantitative in nature, manifested in terms of issues such as preferred levels of exposure to background audioe visual stimulation (Boykin, 1978) or the salience of interruption of daily routines (Roy, Tubbs, & Burton, 2004). Consideration of the issue of sample characteristics emphasizes the need for more factorial and qualitative research on what dimensions of chaos are particularly important for members of other cultures or from different social class groups, as well as research on what contextual characteristics and family coping strategies can attenuate the impact of home chaos in different cultural or economic groups (Wachs & Corapci, 2003;Weisner, 2010).…”
Section: Limitationsmentioning
confidence: 99%
“…The jobs available to welfare recipients are often inconsistent with the demands of parenting, and nonstandard work hours may constrain childcare options Scott et al 2005;Roy et al 2004). In one study, 31% of current and former welfare recipients reported lacking adequate and affordable childcare ).…”
Section: Barriers To Work Among Welfare Recipientsmentioning
confidence: 99%